Substance P/Heparin-Conjugated PLCL Mitigate Acute Gliosis on Neural Implants and Improve Neuronal Regeneration via Recruitment of Neural Stem Cells - Kim, Donghak; Park, DoYeun; Kim, Tae Hee; Chung, Justin J.; Jung, Youngmee; Kim, Soo Hyun (Wiley-Blackwell, 2021)
The inflammatory host tissue response, characterized by gliosis and neuronal death at the neural interface, limits signal transmission and longevity of the neural probe. Substance P induces an anti-inflammatory response and neuronal regeneration and recruits endogenous stem cells. Heparin prevents nonspecific protein adsorption, suppresses the inflammatory response, and is beneficial to neuronal behavior. Poly(l-lactide-co-epsilon-caprolactone) (PLCL) is a soft and flexible polymer, and PLCL covalently conjugated with biomolecules has been widely used in tissue engineering. Coatings of heparin-conjugated PLCL (Hep-PLCL), substance P-conjugated PLCL (SP-PLCL), and heparin/substance P-conjugated PLCL (Hep/SP-PLCL) reduced the adhesion of astrocytes and fibroblasts and improved neuronal adhesion and neurite development compared to bare glass. The effects of these coatings are evaluated using immunohistochemistry analysis after implantation of coated stainless steel probes in rat brain for 1 week. In particular, Hep/SP-PLCL coating reduced the activation of microglia and astrocytes, the neuronal degeneration caused by inflammation, and indicated a potential for neuronal regeneration at the tissue-device interface. Suppression of the acute host tissue response by coating Hep/SP-PLCL could lead to improved functionality of the neural prosthesis.